Variation of climatic and physical co-determinants of phytoplankton community in four nictemeral sampling days in a shallow tropical reservoir, Southeastern Brazil (2002)
ABSTRACT: Spatial and temporal variation of climatic and physical characteristics in a shallow tropical reservoir in the city of São Paulo, Southeastern Brazil, and their possible influence on the dynamics of the phytoplankton population. Samples were taken at 5 depths of the water column (subsurface: 1% Io, 10% Io, 2 m, and bottom) and at 4 hour intervals (6:00, 10:00, 14:00, 18:00, 22:00, 2:00, and 6:00 h) during summer (March 3-4), fall (June 13-14), winter (August 29-30), and spring (November 29- 30) of 1994 at a single sampling station. Garças Reservoir (23o39’S, 46o37’W) is a kinetic turbulent system, highly influenced by winds, with stratification that may last for days or weeks, and which undergoes mixing periods more than once in a year. A thermal pattern of this type is comparable to the warm discontinuous polymictic. Considering its optical properties, the water body was classified as an ecosystem with moderate turbidity, which decreases basically due to increased phaeopigment concentration during the spring. Also, the reservoir is an ecosystem whose phytoplanktonic community is subjected to stress, the degree of which depends on level of light penetration.